Design and implementation of A 2.4GHZ portable active rfid reader system in multi-hop wireless sensor network for indoor tracking - Hashim, Hanis Maisarah (2018)
Warehouse's workers are found to have consumed more time in order to configure the location of the stored products. A quality control for each stock product which has a limited shelf life is lacking as well as present in over-stocking a product. Due to these issues, a portable 2.4GHz active RFID reader system is implemented to overcome the problem. This would be achieved by fulfilling the objectives of the purposed project: To develop a portable 2.4GHz active RFID reader for warehouse management system, to implement it in a real environment and to analyze the performance of the develop system in terms of distance, latency, RSSI and tag collection time. There will be three parts: Monitoring station, RFID reader and RFID tag. Monitoring zone is where the RFID connects to a computer that will display the received data. RFID reader acts as a transceiver which receives and transmits data from RFID tag to the monitoring zone and also may be placed in different positions within the warehouse for providing a continuous inventory control. RFID tag is where the RFID attaches to the product that will transmit its data of the assigned product's information to the RFID reader. The key equipment to receive and send radio signals from RFID tag to the monitoring zone of the purpose work is by using XCTU and Arduino IDE softwares, XBee modules, Arduino boards and power supply. RF module that works on XBee standard (IEEE 802.15.4) will require a development of connection and programming according to its platform. The communication between XBee modules uses an AT command. From the performance analyzation of range test, local RSSI value at Coor-Tx (-68dBm) has better signal strength than Rx-Tag (-72dBm). Meanwhile for latency test, Tx-Coor (3.65Kbps) has a faster average transfer ratio than Tag-Rx (4.28Kbps). Both analyzation show packet lost, thus sending non-reasonable amount of packets by the RFID tag may result in lost of packet.